Service Improvement and Minimization of Complaints on Operational Car Transportation Services at PT X - Davin Sebastian Widjojo; Nova Sepadyati (Jurnal Rekayasa Sistem & Industri, 2023)
PT X is a cigarette company in Indonesia, the problems that occur with the company are related to theprovision of transportation services that are less than optimal because there is no support system toimprove services such as service data has not been recorded real time, division of tasks driver and vehiclesthat are less than optimal, and problems with user complaints because they are not fully met. The averageunfulfilled demand during June-December 2022 is 2.54%, while the company's hope is to fulfil allrequests. The method used to solve the problem is the DMAIC Method along with several tools likeSMART Target, 5 Why Analysis, and RACI Matrix. There are no efforts to deal with the problem supportsystem is to analyze business process early and create a TOSS system framework (Transport SupportSystem) to support transportation services. The effort to overcome user complaints is to use 5Why Analysisand cooperate with external transportation service providers. The implementation of the work was carriedout for two months and had a good impact, namely the average unfulfilled demand decreased to 0.47%.Controlling the results of repairs is by following the system work step design and using the RACI Matrix.